L’Ibaḍisme au XIIème siècle: la ʿAqida de Abu Sahl Yaḥyà (suite) - Cuperly, Pierre (Revue de l'Institut des Belles Lettres Arabes, 1979)
Keywords: Foi -- Traité -- 12e siècle

L’Ibaḍisme au XIIème siècle: la ʿAqida de Abu Sahl Yaḥyà - Cuperly, Pierre (Revue de l'Institut des Belles Lettres Arabes, 1972)
Cuperly gives a biography of the author, a list of his works (with additions and corrections to Schacht 1956, 375-398), a general analysis of the Risāla and a description of each chapter, and a translation of extracts, with notes.
Keywords: Foi -- Traité -- 12e siècle

آراء الخوارج الكلامية: الموجز لأبي عمار عبد الكافي الأباضي - عبد الكافي, أبو عمّار (الشركة الوطنية للنشر والتوزيع, 1978)
Keywords: Foi -- Traité -- 12e siècle